Christianity in England from Roman times to the Reformation ; v. 3 - Hylson-Smith, Kenneth (London, UK SCM, 1999)
This final volume in the author's trilogy places the English Reformation within the context of the late medieval church and also within the framework of the European Reformation as a whole. The book is intended for a broad readership.
Contents : v.3 : 1384 to 1558
Includes bibliographical references and index.
Keywords: Church history -- 1354 - 1558 -- England